Pendampingan Mahasiswa Dalam Aksi Kebersihan Lingkungan Di Kampung Bugis Km. 10 Kota Sorong - Nurbia Nurbia; Azwar Rahmatullah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Students as the younger generation, have a responsibility to change the environment. By creating change and being role models for their communities, students are seen as agents of change. This role can be started by reducing waste and encouraging other people to do positive things to increase awareness of the environment. With this assistance, students were directed to carry out environmental cleanliness actions in Bugis Village Km.10, Sorong City, involving various participants. This action aims to increase the awareness and concern of 40 participants about protecting the environment. In implementing environmental cleanliness actions, the process of sorting waste and transporting recyclable and non-recyclable waste is carried out for disposal at the landfill. The results of the environmental cleanup action obtained 871 kg of inorganic waste, 4,101 kg of residual waste, and 1,476 kg of mixed waste.